Temperature loggers decrease costs of determining bird nest survival - Flavio Sutti; Allan M. Strong (Wildlife Society Bulletin, 2014)
ABSTRACT We tested whether temperature loggers (iButtons®) placed inside bird nests could be used to estimate the date the nest hatched or failed and compared their efficiency and cost to observational data. Temperature loggers were more precise (approx. 1 hr error vs. 1–3‐days error for researcher visit) in estimating fate date for 28 nests of 15 species of birds monitored in the Champlain Valley of Vermont (USA) between May and August 2010. Our nest sample represented a wide range of nest characteristics, and considerably expanded the range of species whose nests have been monitored successfully with temperature data loggers. The use of iButtons would have reduced the number of visits to the nest by 15%, decreasing disturbance, and allowing for more time spent searching for additional nests, or for employment of a smaller field crew. © 2014 The Wildlife Society.